Methods of optimal stabilization of parameters by the production flow line - Pihnastyi, O. M. (Національний технічний університет "Харківський політехнічний інститут", 2020)
The report presents the main directions of research into stabilization systems for flow parameters of production lines at the macroscopic level of description. The models of the flow description of a controlled production process based on the kinetic representation of the technological process are considered.
Keywords: production line; PDE-model of production; distributed system; flow production